Green Synthesis of a Cu/SiO2 Catalyst for Efficient H2-SCR of NO - Gioria, Esteban Gaston (2019)
In this work, the synthesis of Cu/SiO2 catalysts starting from pre-formed copper nanoparticle (CuNP) colloidal suspensions was carried out. Two different protocols for the CuNP synthesis were tested: (i) a green approach using water as solvent and ascorbic acid as reducer and stabilizing agent, and (ii) a second solvothermal method involving the use of diethylene glycol as solvent, sodium hypophosphite (NaH2PO2) as reducer, and polyvinylpyrrolidone (PVP) and cetyltrimethylammonium bromide (CTAB) as stabilizing agents. In addition, and for the sake of comparison, a third catalyst was prepared by solid state conventional grinding of CuO with SiO2. The catalysts were tested in the environmentally relevant catalytic reduction of NOX with H2, in a temperature range from 300 to 500 °C. The catalysts were characterized by X-ray diffraction (XRD), temperature programmed reduction (TPR) cycles, Raman spectroscopy, and N2 adsorption for specific surface BET measurements. From these techniques CuO and Cu(0) species were detected depending on the synthesis protocol. CuNP size and size distribution in the colloid suspensions were determined by transmission electronic microscopy (TEM). The catalyst prepared from the aqueous suspension (CuAsc/SiO2) exhibited higher NO conversion (100%) and selectivity (85%) toward N2 at the lower reaction evaluated temperature (300 °C). The CuCTAB/SiO2 catalyst obtained by the solvothermal approach showed activity at high reaction temperature (400 °C) preferentially. The metal?support mechanical mixture exhibited a negligible response at low temperature and low conversion (68%) and selectivity (88%) at 500 °C. Nanoparticle size and distribution on the support, together with the metal?support interaction, were postulated as the most plausible parameters governing the catalytic performance of the different Cu/SiO2 materials.